The role of pharmacists in the management of AKI patients: What recent studies added to our knowledge? - Abdul Rahman Mahmoud F. Nahas (Society of Diabetic Nephropathy Prevention, 2023)
Introduction: Acute kidney injury (AKI) is a complex syndrome requiring special management. It also complicates the prognosis of many hospitalized patients. Some essential yet nephrotoxic medications and the use of certain procedures that may alter renal hemodynamics further complicate the management of AKI patients. Fortunately, as part of the renal care team, pharmacists can have a significant role in the multidisciplinary approach used to optimize renal patients' health-related quality of life by delivering safe and effective pharmaceutical care. Objective: The present review aims to explore pharmacists' contributions to the management of patients with AKI as well as their influence on improving renal patients' care. Methods: An online search was performed in the databases PubMed, Scopus, and ScienceDirect for relevant articles published in English between 1 January 2015 and 31 December 2021. Review articles, books, guidelines, websites, and conference proceedings were excluded. Results: Only 12 articles out of 51 initially gathered met the eligibility criteria for this review. The three main roles that pharmacists play in the management of AKI patients are patients' education, collaborating with other renal care practitioners, and identifying and solving drug-related problems (DRPs). The latter task span includes medication reconciliation, dosage adjustments, and identifying adverse drug reactions. Conclusion: In view of the complexity of the AKI course, trained pharmacists, as members of the renal care team, can play a pivotal role in managing AKI patients and minimizing their medications burden. This can positively impact the overall renal care process as well as the patient's outcome. Further studies can provide more support to the importance of pharmacists' role in managing AKI.